A extensão universitária na formação docente do curso de pedagogia do IEAA: um olhar para as experiências discentes nos projetos de literatura - Ferreira, Cleonilde Sousa (Brasil, 2021)
This Course Conclusion Work is part of the theme of teacher training and university extension as a contribution to formative experiences in the university / community relationship. Thus, its main objective was to show how the extension projects aimed at children's and juvenile literature contributed to the formation of students included in these projects in the context of Humaitá/AM. This is a documentary research of a descriptive character in which we sought to show how students perceive their insertions in the Extension Curriculum Activities Projects (PACE) from their written reports linked to the final report of each project. For the proper theoretical foundations, support was sought from authors who discuss teacher training, as well as training based on the relationship between theory and practice. The results show that the PACEs aroused in academics the idea that the literate subject is the one capable of developing their knowledge based on their reading of the world and that extension actions as they participated can expand this repertoire of readings. They also point out that, through their participation in PACEs, students realized the importance of participating in extension activities aimed at the theory/practice relationship in teacher education. The advance in students' knowledge regarding reading was a visible point in their reports.